Persepsi Masyarakat Terhadap Aktivitas Produksi Alkohol di Desa Bekonang Berdasarkan Latar Belakang Sosio-Kultural - Uswatun Nikmah; Nur Aida Farani; Faza Mayestha Aji; Alif Akbar Irfansyah; Vita Tranismawati; Negal Hendriyanto; Siti Hadiyati Nur Hafida (Universitas Mataram, 2022)
Industri has a very big important role in life as a leading sector where industrial activities can increase and spur the development of other sectors such as the trade sector, agriculture, and even the service sector. Currently, there are various types of industri, one of which is industri, one of which is the home alcohol industri central java, precisely in Sentul, Bekonang village, Mojolaban district, is one of the areas that has an alcohol or etanol industri. The purpose of the study was to determine the attitudes and views of the Bekonang village community and its surroundings towards the existence of the alcohol industri in Sentul hamlet, Bekonang village, Mojolaban District. In this study using a descriptive method whith a quantitative approach and data collaction techniques used in this research are literature study, interviews, questionnaires, and observation. The conclusion of this study is that some of the Bekonang design communities have a positive influence on the existence of the alcohol industri in Bekonang village. While some people feel disturbed by the alcohol industri waste.